Nueva narrativa hispanoamericana - SHAW, Donald L. (CATEDRA, 1988)
Contiene a:Arlt,R.; Fernández,M.; Borges, Jorge Luis; Marechal,L.; Mallea,E.; Sábato,E.; Onetti,J.C.; GARCIA MARQUEZ, Gabriel; Rulfo,J.